2005
DOI: 10.1029/2004ja010958
|View full text |Cite
|
Sign up to set email alerts
|

Coronal mass ejections and other extreme characteristics of the 2003 October–November solar eruptions

Abstract: [1] Fast coronal mass ejections (CMEs), X-class flares, solar energetic particle (SEP) events, and interplanetary shocks were abundantly observed during the episode of intense solar activity in late October and early November 2003. Most of the 80 CMEs originated from three active regions (NOAA ARs 484, 486, and 488). We compare the statistical properties of these CMEs with those of the general population of CMEs observed during cycle 23. We find that (1) the 2003 October-November CMEs were fast and wide on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
229
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(240 citation statements)
references
References 46 publications
(67 reference statements)
11
229
0
Order By: Relevance
“…Fig. 20 Correlation of CME kinetic energy with GOES peak flux, based on the Halloween flare data given by Gopalswamy et al (2005) …”
Section: Energy Transportmentioning
confidence: 99%
“…Fig. 20 Correlation of CME kinetic energy with GOES peak flux, based on the Halloween flare data given by Gopalswamy et al (2005) …”
Section: Energy Transportmentioning
confidence: 99%
“…Interacting CMEs associated with Type II radio burst cause solar energetic particles as listed by Gopalswamy et al(2001b). Type II radio burst occurring at all wavelengths from metric to kilometric are associated with most energetic CMEs (Gopalswamy et al,2005). Long wavelength radio emission in decameter-hectometric (DH) wavelength from 1kHz to 14 MHz frequency range is important to understand the effects of CME in the outer corona and in the IP medium.…”
Section: Introductionmentioning
confidence: 99%
“…Solar active regions produce CMEs with near-Sun speeds around or excess of 900 km/s [e.g., Sheeley et al, 1999] as well as solar flares. Gopalswamy et al [2005] reported that part of the most energetic (X-class) flares are associated with fast CMEs. Hence, large flares (X-class) correlate to the fast CMEs, which cause the large geomagnetic storms.…”
Section: Resultsmentioning
confidence: 99%
“…Solar active regions can produce CMEs with near-Sun speeds in excess of 900 km/s [e.g., Sheeley et al, 1999] and solar flares. Gopalswamy et al [2005] reported that part of the most energetic (X-class) flares are accompanied by fast CMEs. Based on the statistics from 103 events, Howard and Tappin [2005] found that approximately 40% of the X or M class flares were associated with observed shocks in the solar wind at Earth.…”
Section: Introductionmentioning
confidence: 99%